ANALISIS KESALAHAN BERBAHASA PADA KOMUNIKASI KELUARGA MASYARAKAT DESA LUNDO JAKEN PATI - Rahmadani Indria Fatikhasari; Atiqa Sabardila (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2021)
This study aims to describe the form of language errors in community conversations in Lundo Village, Jaken District, Pati Regency when communicating. This research method uses a qualitative descriptive method. In this study, the data obtained were words, phrases, clauses, and sentences from community conversations in Lundo Village, Jaken District, Pati Regency. The source of this research data is taken from the community at the time of communication. Data collection techniques using interview techniques and audio recording. The results of this study found that language errors in community communication contained 3 error areas, namely (1) phonological errors, (2) morphological errors, (3) syntax errors. Keywords : language errors, communication, society